Social Choice in an Islamic Economic Framework - Masudul A. Choudhury (International Institute of Islamic Thought, 1991)
In this paper, the decision-making character of shura, the consultative democratic concept in an Islamic social order, will be shown to clearly define the determination of both state variables (socioeconomic variables) and policy variables and the simulative interactions between them. These variables will then be shown to configure the consumption, production, and distribution menus in an Islamic political economy. They will thus be shown as clearly defined variables that help to formulate the social choice, the social welfare function, and the institutional decision-making problems in an Islamic politicoeconomic order. Shuratic Decision Making in the Perspective of Organizational Theory The Islamic shuratic (i.e., based on shura) decision-making process is the centerpiece of organhtional behavior in Islamic institutions. The following is a technical explanation of this process in light of modem organizational theory:’ (a) Shura is structured into representative decision makers from various walks of life (“sharees”). (b) “The abstract nature of each individual task” is carried out by ijtihad and the interpretations and implementation of the Shari’ah (Islamic law) to various socioeconomic problems ...